Telephone-based aftercare groups for family carers of people with dementia - results of a mixed-methods process evaluation of a randomized controlled trial - Susanne Lessing; Ruth Deck; Martin Berwig (BMC, 2023)
Abstract Background Caring for a relative with dementia can be demanding and time-consuming. It is not uncommon for them to be overburdened and overworked, which can lead to symptoms of depression or anxiety disorders in 2/3 of cases. One possibility for treating family carers who have these issues is special medical rehabilitation (rehab). However, studies have shown that while such rehab is effective, it is not sustainable. To increase the sustainability of rehab for this target group, structured telephone-based aftercare groups were implemented in the present study. A process evaluation was conducted focusing on the acceptability of the aftercare programme and its perceived benefits by the participating family carers and group moderators. Methods The process evaluation was embedded in a longitudinal randomized controlled trial and followed a mixed methods approach. Quantitative process data were collected using protocols and structured brief evaluations regarding the telephone-based aftercare groups. To assess the acceptability of the aftercare groups as well as their subjective evaluation by the participants, qualitative process data were collected through two longitudinal telephone-based interviews with a subsample of family carers as well as a focus group interview with the group moderators. Results Telephone-based aftercare groups provide acceptable and supportive experiences, and they are shown to be practicable. The content structure and the procedure of the group sessions could be easily implemented in everyday life after inpatient rehab. The topics addressed with each patient were met with a consistently positive response. Learning from the other group members and sharing a bond based on the experience of caring for a relative with dementia were evaluated as positive outcomes in the group. The universality of suffering as a central effective factor of group psychotherapy also played a decisive role in this telephone-based support group format for a shared bonding and strengthening experience in the groups and thus for their effectiveness. Conclusion Telephone-based aftercare groups for family carers of people with dementia are a useful and acceptable tool in the context of rehab aftercare. This location-independent aftercare programme could be adapted for other indications, focuses or topics in everyday care. Trial registration German Clinical Trials Register: DRKS00013736, 14/05/2018.